2012
DOI: 10.1073/pnas.1205880109
|View full text |Cite
|
Sign up to set email alerts
|

Connexin 43 controls the multipolar phase of neuronal migration to the cerebral cortex

Abstract: The prospective pyramidal neurons, migrating from the proliferative ventricular zone to the overlaying cortical plate, assume multipolar morphology while passing through the transient subventricular zone. Here, we show that this morphogenetic transformation, from the bipolar to the mutipolar and then back to bipolar again, is associated with expression of connexin 43 (Cx43) and, that knockdown of Cx43 retards, whereas its overexpression enhances, this morphogenetic process. In addition, we have observed that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 50 publications
3
46
0
Order By: Relevance
“…5A and Fig. S3), consistent with an idea that Cx43 plays an important role in tangential migration and maturation of GABAergic neurons, as it does in radial migration of glutamatergic cells (45,46).…”
Section: +supporting
confidence: 74%
See 1 more Smart Citation
“…5A and Fig. S3), consistent with an idea that Cx43 plays an important role in tangential migration and maturation of GABAergic neurons, as it does in radial migration of glutamatergic cells (45,46).…”
Section: +supporting
confidence: 74%
“…Gap junctions and hemichannels have been broadly implicated in the control of embryonic patterning of the neocortex, including neuronal proliferation, maturation, and differentiation (45,46). Gap junctions contribute to the generation of cortical circuits by mediating oscillatory patterns of electrical activity in the neonatal mouse cerebral cortex (7,22,47) and are an important means of intracellular communication at this age (46,48 5A).…”
Section: Extracellular Camentioning
confidence: 99%
“…Cx43 is a major gap junction channel that has been implicated in neural development of the embryonic brain (29,(31)(32)(33)(34). Expression of Cx43 in ES cell-derived neural progenitors expressing nestin was confirmed with immunocytochemistry ( Fig.…”
Section: Resultsmentioning
confidence: 82%
“…Inotropic purinergic P2X3 receptors are expressed in dental pulpal nerve fibers (Alavi et al 2001), which supports a role for ATP signaling in mediating dentin hypersensitivity and dental pain (Magloire et al 2010). Previous work found that odontoblasts express the gap junction/hemichannel protein connexin 43, which mediates ATP release upon intracellular and extracellular stimulation with 0mM Ca , and NO signals (Retamal et al 2009;Liu et al 2010;Nakagawa et al 2010;Liu, Sun, et al 2012). Therefore, ATP released from odontoblasts could then activate nearby P2X3 receptors on dental pulp nerve fibers to depolarize the membrane potential and initiate the nociception signals for dentin hypersensitivity.…”
Section: Discussionmentioning
confidence: 99%